Antioxidant, bioactive, and nutritional potential of soybeans with brown and yellow seed coats - Victor Delino Barasuol Scarton; Ivan Ricardo Carvalho; Christiane de Fátima Colet; Jaqueline Piesanti Sangiovo; Willyan Júnior Adorian Bandeira; Murilo Vieira Loro; Ellen Cristina Perin; Solange Teresinha Carpes; Patricia Brugnerotto (Revista Ciência Agronômica)
ABSTRACT The use of soybeans for human consumption is primarily attributed to their high protein content and diverse phytochemical composition, which are key for improving human nutrition. Given the growing interest in biofortification to enhance the nutritional value of crops, this study aimed to assess the agronomic performance, nutritional, functional and physicochemical composition of soybean lines with both brown and yellow seed coats, with a particular focus on their biofortification potential. To achieve this, we evaluated ten F6 generation soybean genotypes (G1M, G2M, G3A, G4A, G5A, G6A, G7A, G8A, G9A, and G10A), along with a commercial control (G11T), using a randomized block design. Sowing occurred in the second half of November 2020, and after harvesting, grain samples were analyzed for agronomic and biochemical traits, including fatty acids, neutral and acid detergent fibers, minerals (Na and K), proteins, lipids, total flavonoids, total phenolic content, and antioxidant activity (ABTS and FRAP). A previous experiment with extractive conditions related to temperature and extraction method was carried out to evaluate the antioxidant properties. Significant variation in agronomic and proximate traits was observed among the genotypes, and the interaction between genotypes and extraction methods notably influenced antioxidant properties. Genotypes with brown seed coats, particularly G2M, showed high potential for protein and oleic acid content, making them suitable for biofortification and food product applications. The Ultrasonic Bath extraction method proved more effective in extracting ABTS and total flavonoids. These findings suggest that both the seed coat color and extraction method play crucial roles in determining the bioactive and nutritional potential of soybeans, supporting their use in biofortification strategies for enhanced human nutrition.